Association between oxidative balance score and systemic immune-inflammation index: NHANES 2003–2018 - Yongling Niu; Ziyi Fan; Zelin Wang; Shufen Liang (PLoS ONE, 2025)
Background As we all known oxidative stress and inflammation were interdependent and interconnected. Oxidative balance score (OBS) could assess the antioxidant capacity of an individual’s body. The purpose of this study sought to investigate the connection between OBS and the recently proposed inflammatory indicator——Systemic immune-inflammation index (SII). Methods The study incorporated 16,080 participants from National Health and Nutrition Examination Survey (NHANES) database (2003–2018). We utilized weight multivariable linear regression analyses to assess this association. Additionally, subgroup analyses and linear relationships were performed for deeper insights. The robustness of the findings was ensured by conducting multiple sensitivity analyses. Results In the multivariate model using the first OBS category as the reference, higher OBS quartiles had a significantly negative association with SII [β = −51.52 (95%CI: −68.31, −34.73), P for trend < 0.001]. The interaction test showed that age (P < 0.001) and hypertension (P = 0.043) had a significant effect on this connection. Restricted cubic splines plot with four knots illustrated a linear relationship between OBS and SII (P-non-liner = 0.677). The findings from the sensitivity analysis aligned with the outcomes of the primary analysis, confirming the consistency and reliability of the results. Conclusions OBS based on diet and lifestyle had a strongly negative association with SII. This study emphasized the importance of improving an individual’s overall antioxidant status through diet and lifestyle changes, highlighting its effectiveness in reducing inflammation index.